PHYSICAL FITNESS RELATED TO HEALTH IN WOMEN PHYSICALLY ACTIVE (Fiep Bulletin - online, 2014)
Introduction: Lack of physical activity is not good to health. Physical fitness promotes health benefits. Aim: The objective of the study was to evaluate the physical fitness related to health in physically active women. Methodology: Data were collected from 35 female volunteers between 22 and 49 years in the city of Aracaju, state of Sergipe, Brazil. The average age of women participating in the study was 31.51 ± 6.74 years with a mean and standard deviation in height of 1.59 ± 0.05 meters, body mass 63.90 ± 9.20 kg and body mass index (BMI) of 25.28 ± 3.18 kg/m2 . The tests performed were: Bank of Queen's College Test, Sit and Reach Test,  Resistive Force Test Extension and Flexion of the elbow (arm flexion) and Abdominal Strength Test. It was also evaluated the VO2 max obtained, VO2 max predicted, aerobic functional deficit (FAI). Results: It was found the following tests values for: abdominals 36.68 ± 13.64 repetitions, in the arm flexion 14.82 ± 10.12 repetitions, in flexibility 29.94 ± 7.36 cm, in VO2max predicted 40 , 12 ± 2.78 ml.kg.- 1min.- 1, in VO2max obtained 38.44 ± 3.87 ml.kg. -1min. - 1 and FAI of 13.56 ± 4.03 % . This shows good results for testing abdominal strength , excellent for arm flexion, regular to flexibility and good for VO2max . The FAI showed no significant deficit. Conclusion: The physically active women had a good physical fitness, despite being qualified in BMI as overweight.
Keywords: Health; physical fitness; exercise.